Penyimpangan Orientasi Seksual (Kajian Psikologis dan Teologis) - Ayub Ayub (University of Darussalam Gontor, Indonesia, 2017)
Recently, the issues of Lesbian, Gay, Biseksual and Transgender has attracted the attention of public More, Nationally and internationally. it is ironic that some territories of the United State has declared legality of LGBT’s activity officially, when the activity is obviously a kind of sexual orientation deviation. moreover, they have several argumets to strengthen the legalization; they said the status of LGBT has changed from sexual orientation deviation to ordinary orientation as confirmed by the psychology master book “Diagnostic and Statistic Manual of Mental disorder (DSM)”. They also try to desconstruct syariah law to strengthen the arguments theologically. This paper attempts to reveal the facts behind the LGBT movement, by tracking the historical background of how they could compromize with the legality of LGBT’s activities. in the end, it sould be explained how the religions, expecially Islam, view this problem of sexual orientation.